PENGARUH DIGITALISASI PERPAJAKAN DAN LITERASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI ERA IMPLEMENTASI CORE TAX SYSTEM - Clara Felicia Regina Francis; Kadek Wulandari Laksmi P (Juremi: Jurnal Riset Ekonomi, 2026)
The Core Tax System's deployment is a strategic move to digitally change tax administration and increase the effectiveness, accuracy, and transparency of tax services. The degree of tax literacy among the general population, which has a big impact on taxpayer compliance behavior, is crucial to the efficacy of digital tax systems. This study uses Attribution Theory as its theoretical framework to investigate how individual taxpayers' compliance in Denpasar City is impacted by both external (tax digitization) and internal (tax literacy) factors. Purposive sampling was used to select 150 respondents, and questionnaires were distributed as part of a quantitative research approach. Multiple linear regression, instrument validity and reliability tests, and traditional assumption tests were used to examine the collected data. The findings show that tax digitalization significantly and favorably affects taxpayer compliance, suggesting that better system integration and accessibility boost compliance. Additionally, there are positive and significant effects of tax literacy, indicating that a thorough understanding of tax rights, obligations, and processes encouraging compliance conduct. These findings highlight the importance of synergizing digital system optimization with strengthened tax education efforts.